Assisting design ideas: PToolkit, a pilot study - Saidin, Aeni Zuhana; Shaari, Nassiriah; Alwi, Asmidah (UTM Press, 2015)
Design for persuasion requires the designer to understand theories, ideas and strategies of persuasion that could change, modify or adapt people’s behavior.This situation requires the designer to access appropriate persuasion knowledge by making the design suit to the persuasion intention. Therefore, a tool called as PToolkit was introduced to assist designer during the design process. Then, a pilot evaluation was conducted to evaluate PToolkit.This is to ensure that the actual evaluation phase would run smoothly, as well as having an initial understanding of the ability of PToolkit in influencing the design ideas.As a result, few evaluation procedures were amended and ways of data interpretation were suggested.